‘On Both Sides of the Strait’: Discourses and Policies on Cultural Diversity in Southern Mediterranean Spain - Venegas, Mar; Luque, Mónica; Velasco, Elisa; Sánchez, Kiko (Revista Española de Sociología, 2023)
This article aims to analyse the evolution, and current situation, of discourses and policies on cultural diversity in primary schools on both sides of Southern Mediterranean Spain around the Strait of Gibraltar (Andalusia, Murcia, Ceuta and Melilla). To do so, the methodology designed is based on two techniques: documentary analysis of secondary sources (regulations, statistics) and personal interviews with administrative and political personnel from the regional education administration (discourses). Based on the data analysed, the article shows how the arrival of students of foreign origin in the 1990s stimulated education policies of exogenous cultural diversity, whereas endogenous cultural diversity is inherent to historically multicultural societies (‘diversicracy’). The data lead to the conclusion that there is a need to re-politicise educational policy on cultural diversity to promote interculturality based on citizenship rights and social justice, for which a rights-based approach is particularly appropriate.